Changes in Gallbladder Motility and Gallstone Formation Following Laparoscopic Gastric Banding for Morbid Obesity - Bilal O Al-Jiffry; Eldon A Shaffer; Gino TP Saccone; Peter Downey; Lilian Kow; James Toouli (Canadian Journal of Gastroenterology)
Morbid obesity is associated with cholesterol gallstone formation, a risk compounded by rapid weight loss. Laparoscopic gastric banding allows for a measured rate of weight loss, but the subsequent risk for developing gallstones is unknown.